2014
DOI: 10.21065/19204159.6.55
|View full text |Cite
|
Sign up to set email alerts
|

Development of Uv Spectrophotometric Methods and Validation for Estimation of Simvastatin in Bulk and Tablet Dosage Form by Absorbance Maxima and Area Under the Curve Method

Abstract: To develop two simple UV spectrophotometric methods for simultaneous estimation of Simvastatin (SMV) in bulk and tablet dosage form and validate as per ICH guidelines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…FRS was successfully estimated in its pharmaceutical preparations by the suggested method. The numerical results in (Table 4 ) show a good agreement and conformity with those obtained from the comparison method [ 4 ]. Variance ratio F-test and Student’s t-test [ 26 ] were used to statistically analyze the results obtained by both methods.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…FRS was successfully estimated in its pharmaceutical preparations by the suggested method. The numerical results in (Table 4 ) show a good agreement and conformity with those obtained from the comparison method [ 4 ]. Variance ratio F-test and Student’s t-test [ 26 ] were used to statistically analyze the results obtained by both methods.…”
Section: Resultssupporting
confidence: 73%
“…The values of LOD and LOQ proved that the suggested method is sufficiently sensitive as summarized in Table 1 The accuracy of the proposed method was confirmed by calculating the mean % recoveries of raw material of FRS. The comparison method [ 4 ] depends on measuring the absorbance of FRS at 277 nm in methanol. Variance F-test and Student’s t-test were used to compare the results obtained from the comparison and proposed method as illustrated in (Table 2 ) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodents are largely used to study drug effect on body systems in preclinical studies, but researchers do not use analytical methods as a routine to detect and monitor the drug 12 µg/mL. In our study, we followed the protocol described by Chavhan et al, 20 and we have found a maximum absorption at 300 nm. Regarding the TEL linear function range for detection, we decided for 1.25-60 µg/mL based on the goodness of curve fit of the linear regression.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we evaluated if it is possible to measure the TEL concentration and stability in the drinking water offered to mice. To accomplish that, we used the method of UV spectrophotometry proposed by Chavhan et al to measure the TEL concentration in the mice drinking water 20 …”
Section: Introductionmentioning
confidence: 99%